Vlasta Jalušič and Wolfgang Heuer (Eds.): What Kind of Government? Rethinking Contemporary Forms of Government after the Break in Tradition. - Koper, Adam John (HannahArendt.net, 2025)
Vlasta Jalušič and Wolfgang Heuer (Eds.): What Kind of Government? Rethinking Contemporary Forms of Government after the Break in Tradition.